Principles of Systems Science - Mobus, George E.; Kalton, Michael C. (Understanding Complex Systems,, 2015)
This pioneering text provides a comprehensive introduction to systems structure, function, and modeling as applied in all fields of science and engineering. Systems understanding is increasingly recognized as a key to a more holistic education and greater problem solving skills, and is also reflected in the trend toward interdisciplinary approaches to research on complex phenomena. The subject of systems science, as a basis for understanding the components and drivers of phenomena at all scales, should be viewed with the same importance as a traditional liberal arts education. Principles of Systems Science contains many graphs, illustrations, side bars, examples, and problems to enhance understanding. From basic principles of organization, complexity, abstract representations, and behavior (dynamics) to deeper aspects such as the relations between information, knowledge, computation, and system control, to higher order aspects such as auto-organization, emergence and evolution, the book provides an integrated perspective on the comprehensive nature of systems. It ends with practical aspects such as systems analysis, computer modeling, and systems engineering that demonstrate how the knowledge of systems can be used to solve problems in the real world.  Each chapter is broken into parts beginning with qualitative descriptions that stand alone for students who have taken intermediate algebra. The second part  presents quantitative descriptions that are based on pre-calculus and advanced algebra, providing a more formal treatment for students who have the necessary mathematical background. Understanding these basics enables further understanding both of how systems endure and how they may become increasingly complex and exhibit new properties or characteristics. ·         Serves as a textbook for teaching systems fundamentals in any discipline or for use in an introductory course in systems science degree programs ·         Addresses a wide range of audiences with different levels of mathematical sophistication ·         Includes open-ended questions in special boxes intended to stimulate integrated thinking and class discussion ·         Describes numerous examples of systems in science and society ·         Captures the trend towards interdisciplinary research and problem solving.